2019
DOI: 10.2478/mmcks-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Brand Love as Mediator of the Brand Experience-Satisfaction-Loyalty Relationship in a Retail Fashion Brand

Abstract: Framed by the consumer-brand relationship theory, this paper investigates the path from the brand-consumer behaviour interaction to the relationship durability and stability, through brand relationship quality. Specifically, it examines brand experience as an antecedent of brand love, and customer loyalty and satisfaction as outcomes in the retail setting. Based on 560 customers' responses to a face-to-face questionnaire administered in a fashion brand retail store, research hypotheses were tested using a stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 42 publications
(73 reference statements)
6
35
0
3
Order By: Relevance
“…The outcome of this finding is not surprising because when banks are involved in CSR activities, customers would develop respect towards their brand, which would eventually lead to trust. The result of H5 confirmed that when customers are satisfied with the services and product of an organization, they love the brand, which, in turn, translates into loyalty, supported by previous studies conducted by scholars such as Mody and Hanks (2020), Song et al (2019), andFerreira et al (2019).…”
Section: Discussion Of Results and Contributionssupporting
confidence: 72%
“…The outcome of this finding is not surprising because when banks are involved in CSR activities, customers would develop respect towards their brand, which would eventually lead to trust. The result of H5 confirmed that when customers are satisfied with the services and product of an organization, they love the brand, which, in turn, translates into loyalty, supported by previous studies conducted by scholars such as Mody and Hanks (2020), Song et al (2019), andFerreira et al (2019).…”
Section: Discussion Of Results and Contributionssupporting
confidence: 72%
“…In current market dynamics, brand love is also essential (Rodrigues and Rodrigues, 2019), and it is a newly applicable concept in recent research studies (Bairrada et al , 2018). Previously, the construct of brand experience and brand love was measured through various concepts such as brand loyalty, customer engagement, positive word of mouth and customer loyalty in Europe (AŞKin and İlayda, 2016; Bıçakcıoğlu et al , 2018; Ferreira et al , 2019; Prentice et al , 2019; Rodrigues and Rodrigues, 2019). In the same way, brand experience and brand love were measured through effective commitment, brand loyalty and behavioral intentions in Asia (Garg et al , 2016; Gumparthi and Patra, 2019; Huang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, authenticity has become an essential topic of gaining attention from many scholars (Morhart et al , 2015; Napoli et al , 2014). Despite the essential role of brand experience and authenticity for developing brand love, there is a scant of literature on the subject (Das et al , 2019; Ferreira et al , 2019; Keiningham Timothy et al , 2019). As discussed, there are few studies available in the Asian context, while the Asian markets are proliferating and much-debated topic (Fam et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A soft-servicescape may arise when a tourist attaches an ambient response to an experience of social interaction (Tran Quynh, Dang My, & Tournois, 2020) with local people at the destination. Receiving polite responses, support, and feelings of friendship in a destination enhances positive emotions, such as excitement, happiness, and energy (Tubillejas Andrés, Cervera-Taulet, & Calderón García, 2016); this experience may result in a kind of brand love (Ferreira, Rodrigues, & Rodrigues, 2019) to a visited destination.…”
Section: Destination Servicescape Quality and Authentic Value Advantage In The Sdl Perspectivementioning
confidence: 99%